Peningkatan Kemampuan Membaca Puisi Anak dengan Pendekatan Contextual Teaching and Learning (CTL) pada Siswa Kelas V Sekolah Dasar - Sutarti, Sutarti (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2018)
Abstract. This study aims to determine the improvement of children's poetry reading skills with the Contextual Teaching and Learning approach in Class V Students of SDN 2 Nanggulan, District of Cawas, Klaten Regency, Semester I, Academic Year 2018/2019. This Classroom Action Research was conducted in the fifth grade of Nanggulan Elementary School 2 in Cawas District, Klaten Regency with a total of 17 students, consisting of 3 male students and 14 female students. This classroom action research is carried out three cycles in a continuous manner. Each cycle is carried out by planning, implementing, observing, and reflecting to determine the effectiveness of the action. Based on the analysis, it can beconcluded as follows: First, based on observations of teacher performance the results of the average score of teacher performance have increased from learning Cycle I for 1.3 Cycle II learning to 2.3, and at Cycle III 2.7. With the criteria of a sufficient limit score is a score of 2 and a score of 3 is good; Second, based on student activity data for three cycles, the average score about student activity experienced an increase from Cycle I learning at 1.2 learning Cycle II to 2.0 and in Cycle III learning to 2.8; Third, based on the results of the assessment ofreading children's poetry with the Contextual Teaching and Learning approach, the average score of the test results and assignments has increased from Cycle I learning to 70.89 Cycle II learning to 75.59 and Cycle III learning to 79.71 . Increasing the percentage of classical learning completeness by learning cycle I was 41.18%, learning Cycle II became 58.82%, and learning in Cycle III reached 82.35%. Thus through the Contextual Teaching and Learning approach the ability to read children's poetry in Class V students of SD Negeri 2 Nanggulan, District of Cawas, Klaten Regency, in the first semester of school year 2018/2019 can increase.